Cyclodextrin‐Based Multistimuli‐Responsive Supramolecular Assemblies and Their Biological Functions. Issue 3 (18th February 2019) - Zhang, Ying‐Ming; Liu, Yao‐Hua; Liu, Yu
Abstract: Cyclodextrins (CDs), which are a class of cyclic oligosaccharides extracted from the enzymatic degradation of starch, are often utilized in molecular recognition and assembly constructs, primarily via host–guest interactions in water. In this review, recent progress in CD‐based supramolecular nanoassemblies that are sensitive to chemical, biological, and physical stimuli is updated and reviewed, and intriguing examples of the biological functions of these nanoassemblies are presented, including pH‐ and redox‐responsive drug and gene delivery, enzyme‐activated specific cargo release, photoswitchable morphological interconversion, microtubular aggregation, and cell–cell communication, as well as a geomagnetism‐controlled nanosystem for the suppression of tumor invasion and metastasis. Moreover, future perspectives and challenges in the fabrication of intelligent CD‐based biofunctional materials are also discussed at the end of this review, which is expected to promote the translational development of these nanomaterials in the biomedical field. Abstract : Recent progress in cyclodextrin‐based multistimuli‐responsive supramolecular assemblies is systematically reviewed, their biological functions are presented by selecting some representative examples, and future perspectives and challenges in this promising field are discussed.